Belt conveyor tunnel support structure - Živanović Miloš; Miljković Nikola; Stefanović Jelena; Jovanović Nikola; Pavlović Zlatko (Bakar)
This paper will cover the Preliminary Design of the by-products transport system after the Ecological reconstruction of the thermal power plant Pljevlja. The 4.5 km belt conveyor long route enters the tunnel at Borovica Lake. Tunnel position is in relation to the route, the cross-section selection, calculation of structural elements and fitting into the ambient unit around the lake are described.